Occupants' tolerance of thermal discomfort before turning on air conditioning in summer and the effects of age and gender. (1st June 2022) - Jian, Yiwen; Liu, Jingjing; Pei, Ze; Chen, Jiujiu
Abstract: Thermal tolerance, which is the condition of mind of occupants expressing their total unacceptability to the thermal environment after physiological and psychological regulation and any behavioral adjustments other than air conditioning, plays a key role in air conditioner operation behavior in summer. However, literature reviews have illustrated that systematic analysis of thermal tolerance remains a key challenge. Previous studies have mostly focused on high indoor air temperature, but did not reveal the nature of thermal tolerance based on the relationship between the indoor environment, air conditioner switch-on behavior, and thermal responses of the human body. To address these knowledge gaps, the data from a field survey of 54 occupants in Beijing conducted over one summer were used, including physical measurements of environmental parameters and occupants' thermal sensations. In addition to showing indoor air temperature beyond the adaptive thermal comfort zone, this study provides new insights on thermal tolerance by elucidating the temporal deviation between air conditioner switch-on and occupants' thermal unacceptability. This temporal deviation depends strongly on the ages and genders of occupants, highlighting the nature of thermal tolerance. Moreover, the impacts of age and gender were demonstrated to be more reflected in differences in psychological conditions and behavioral and cultural backgrounds than in physiological conditions alone. Thermal tolerance was thus estimated quantitatively using the "discomfort capacity", a cumulative value of the difference between the indoor air temperature and the lower-limit of discomfort temperature during the period of thermal discomfort episodes prior to occupants' turning on the air conditioning in summer, to account for the combined effects of both the environmental stimulus intensity and the duration of discomfort episodes on air-conditioner switch-on. On this basis, for young male, young female, middle-aged male, middle-aged female, and elderly occupants, the average values of the maximum duration of discomfort episodes prior to occupants' turning on air conditioning at various indoor air temperatures were presented, by which occupants' thermal tolerance to hot indoor environment in summer can be intuitively quantified from both the temporal dimension and the intensity of stimulus. This study will be helpful to optimize the operation strategy of air conditioner by minimizing the dependence of occupants on air conditioning, and then to realize energy savings. Highlights: Thermal tolerance makes AC switch-on lagging behind human thermal unacceptability. Thermal tolerance involves both environmental exposure and exposure duration. Thermal tolerance can be estimated quantitatively using the "discomfort capacity". Thermal tolerance exhibits great dependence on occupants' age and gender. Exposure duration at different temperatures is quantified for five groups of occupants.